Emergence and spread of NADC34‐like PRRSV in Southwest China. Issue 5 (4th February 2022) - Zhao, Jun; Xu, Lei; Xu, Zhiwen; Deng, Huidan; Li, Fengqing; Sun, Xiangang; Zhou, Yuancheng; Zhu, Ling
Abstract: In recent years, NADC34‐like PRRSV had a strong impact on the pig industry in the United States and Peru; it was also detected in northeastern China in 2017. In this study, we conducted a retrospective survey of NADC34‐like PRRSV in Southwest China from 2016 to 2020. Five NADC34‐like PRRSV strains were detected in samples and their whole genomes were sequenced, designated as CHSCMY‐22019, CHSCYB‐32020, CHSCMS‐42020 and CHSCLS‐22020. This is the first discovery and report of an NADC34‐like PRRSV strain in Southwest China. Phylogenetic tree analysis based on the whole genome showed that the five NADC34‐like PRRSV strains belonged to sub‐lineage 1.5 of PRRV‐2. They had 100 aa deletions in the Nsp2 hypervariable region of VR2332, located at 329–428 aa, similar to the US isolate IA/2014/NADC34. Recombination analysis showed that CHSCCD‐42020 strain was the recombinant strain of QYYZ strain and IA/2014/NADC34 strain in China. The emergence of NADC34‐like PRRSV strains in Southwest China indicates a potential threat to PRRS prevention and control in pigs. This study improves our understanding of the epidemic status and genetic variation of NADC34‐like PRRSV strains in China.